Perancangan Sistem Pemetaan Ruangan Secara Dua Dimensi Menggunakan Sensor Ultrasonik - Ricky Prasetya Santoso; Wijaya Kurniawan; Gembong Edhi Setyawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Mapping a location is the means used to obtain information from a point at somewhere dangerous or difficult to reach because of the great safety and accidents that can be experienced when seeking information itself is the direct human contact with the dangerous conditions. For that we need a device that can replace humans as subjects to search for an object at a point. Tools designed and realized in this thesis is used to map the room that the results can be viewed on a computer screen in the form of two-dimensional map space. This device consists of an Arduino Uno, HC-SR04 ultrasonik and dc motors. Based on the analysis of the results of system testing performed, the mapping system works well is able to visualize the location of a box in accordance with the previously arranged with an average of 93,1% accuracy of the system